Impact of Implementing a Protocol on the Perioperative Management in Patients Treated with Antithrombotics Admitted for Hip Fracture Surgery: an Observational Study. Issue 5 (25th May 2016) - Iavecchia, Luján; Safiya, Ahmad; Salat, David; Sabaté, Mònica; Bosch, Montse; Biarnés, Alfons; Camps, Angels; Castellà, Dolors; Lalueza, Pilar; Pons, Verònica; Teixidor, Jordi; Villar, Maria M.; et al.
Abstract: This study aimed to describe the impact of implementing a protocol on the perioperative management of patients admitted for hip fracture treated with antithrombotics. A protocol was designed based on the recommendations from the American College of Chest Physicians (ACCP). After its implementation (May 2012), information on antithrombotic management was collected from admission to 3 months after surgery in retrospective (October 2011‐March 2012) and prospective (October 2012‐March 2013) cohorts. Patients' thromboembolic risk was classified into high, moderate or low according to the ACCP categories. A total of 113 and 101 cases were included in the retrospective and prospective cohorts, respectively. No differences in age, gender, American Society of Anaesthesiology score or thrombotic risk categories were observed between cohorts. Most patients were treated with aspirin or triflusal (55.1% and 48.1% in each cohort, respectively), clopidogrel (24.5% and 26.6%) or acenocoumarol (16.3% and 20.2%). In moderate to high thromboembolic risk patients, a higher rate of bridging therapy with full doses of enoxaparin (18.5% and 50%, p = 0.04 before and 9.1% and 43.7%, p = 0.02 after surgery) and a lower rate of aspirin discontinuation (76% and 55.3%, p = 0.03) were observed in the prospective cohort. Both cohorts had a similar percentage of cases with bleeding (68.1% and 68.3%) and thrombotic events (11.5% and 13%). No differences in the timing between surgery and the discontinuation or resumption of antithrombotics were noted. After the protocol implementation, aspirin was less often stopped and bridging therapy with therapeutic doses of enoxaparin was used more often. However, interruption and resumption times of antithrombotics remained almost unchanged. In order to achieve these goals, more efforts should be made to implement the protocol in clinical practice.